2014
DOI: 10.1371/journal.pone.0110200
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Evolution of Riparian Woodlands Facing Climate Change in Three European Rivers with Contrasting Flow Regimes

Abstract: Global circulation models forecasts indicate a future temperature and rainfall pattern modification worldwide. Such phenomena will become particularly evident in Europe where climate modifications could be more severe than the average change at the global level. As such, river flow regimes are expected to change, with resultant impacts on aquatic and riparian ecosystems. Riparian woodlands are among the most endangered ecosystems on earth and provide vital services to interconnected ecosystems and human societ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
45
0
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(56 citation statements)
references
References 80 publications
8
45
0
3
Order By: Relevance
“…Specifically, the expected reduction of 15% in mean annual discharges (Average Flow) was shown to result in the prediction of an overall riparian shrinkage for the 2046-2065 time slice, and a consequent decrease in the lateral and longitudinal connectivity of the riparian galleries. Our results are corroborated by previous studies that identified changes in flow regimes as the main causes of riparian modifications under global warming scenarios (Poff and Zimmerman, 2010;Rivaes et al, 2014). Studies assessing the effect of fluvial disturbance on riparian vegetation dynamics reported a decrease in both the mean patch size and the total area occupied by riparian woodlands, as a consequence of the reduction in natural streamflows caused by water scarcity scenarios (Kominoski et al, 2013;Rivaes et al, 2014).…”
Section: Alterations In Riparian Connectivity and Complexity Under CLsupporting
confidence: 91%
See 1 more Smart Citation
“…Specifically, the expected reduction of 15% in mean annual discharges (Average Flow) was shown to result in the prediction of an overall riparian shrinkage for the 2046-2065 time slice, and a consequent decrease in the lateral and longitudinal connectivity of the riparian galleries. Our results are corroborated by previous studies that identified changes in flow regimes as the main causes of riparian modifications under global warming scenarios (Poff and Zimmerman, 2010;Rivaes et al, 2014). Studies assessing the effect of fluvial disturbance on riparian vegetation dynamics reported a decrease in both the mean patch size and the total area occupied by riparian woodlands, as a consequence of the reduction in natural streamflows caused by water scarcity scenarios (Kominoski et al, 2013;Rivaes et al, 2014).…”
Section: Alterations In Riparian Connectivity and Complexity Under CLsupporting
confidence: 91%
“…More recent research used dynamic hydro-vegetation models to describe the evolution of riparian woodlands and flow relationships with vegetation stages facing climate change (e.g. Rivaes et al, 2013Rivaes et al, , 2014, and to explore the future distribution of species' functional traits in different climate change scenarios (Catford et al, 2012;Rocha et al, 2015). Nevertheless, most studies rely on the single-hydrological perspective, and particularly lack the well documented influence of landuse change on the establishment of riparian structural and compositional patterns (Allan, 2004;Aguiar and Ferreira, 2005;Burton et al, 2005;Hooke, 2006;Fernandes et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Changes in vegetation height and density in floodplain forests in natural systems are mainly due to succession (Primack, 2000;Garssen et al, 2014;Rivaes et al, 2014). The present potential natural floodplain forest is in many areas reduced to narrow fringes accompanying the river, which are flooded at least annually.…”
Section: Potential Changes In Vegetation Covermentioning
confidence: 99%
“…Community changes which might affect vegetation height and density are possible within the next century, though changes in vegetation height and density in floodplain forests in natural systems are mainly due to succession. Primack (2000), Garssen et al (2014) and Rivaes et al (2014) studied the effect of climate change on natural riparian vegetation cover via changes in the hydrological regime including inundation periods and intensity, days since rain and the decline of water table. As the Pinka is anthropogenically influenced and will be regulated for the foreseeable future, no dynamical changes and no natural succession dynamics are expected which could cause an extreme change in vegetation cover.…”
Section: Ability Of Riparian Vegetation To Mitigate the Expected Strementioning
confidence: 99%
“…Disturbances on riparian vegetation can be classified into two categories suggested in this research: natural and anthropogenic ones. Many studies classify climate changes as the primary natural disturbance on riparian vegetation (Martin, 1993;Politti et al, 2014;Rivaes et al, 2014;Witte et al, 2014), which affect riparian vegetation primarily through climate-driven hydrologic changes. Climate change in the Alpine floodplain is an example of a natural disturbance: as a relatively discrete event, climate change scenarios create regression or succession processes .…”
Section: Disturbancesmentioning
confidence: 99%